Undergraduate Students\' Perceptions Toward Inventing Web-Based Learning For Drawing Class - Omar, Nurul Nisa (2011)
Technology has been growing drastically since 1999. Since then, the process of education has also been altered, changed and transformed alongside the usage of technology. (Bonk & King, 1998). As result, many types of web-based education products has been created such as; online tutorial, e-learning website, video conferences and a lot more. These are also called products of web-based learning.